2008
DOI: 10.1089/jwh.2007.0353
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the Use of Antiretroviral Treatment in Resource-Constrained Settings: Findings from a Multicenter Collaboration

Abstract: Women in resource-constrained settings are not necessarily disadvantaged in their access to HAART. More attention needs to be paid to ensuring that HIV-infected men are seeking care and starting HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
165
4
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 186 publications
(198 citation statements)
references
References 20 publications
27
165
4
2
Order By: Relevance
“…Proportionally, more females were found to be adherent to HAART compared to males with statistical significance (p 5 0.015). This finding is similar to that reported by Braitstein and colleagues, following a review of ART in low-income countries in Africa, Latin America, and Asia that found more women assessing and adherent to HAART and less likely to have advanced HIV [28]. A South African study reported similar finding [39].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Proportionally, more females were found to be adherent to HAART compared to males with statistical significance (p 5 0.015). This finding is similar to that reported by Braitstein and colleagues, following a review of ART in low-income countries in Africa, Latin America, and Asia that found more women assessing and adherent to HAART and less likely to have advanced HIV [28]. A South African study reported similar finding [39].…”
Section: Discussionsupporting
confidence: 90%
“…Gender disparity in access to HAART, as observed in this study, was also observed in a multicenter study in 13 lowincome countries, where a male-female ratio of 2:3 was found [28]. In addition, Bello et al reported that the proportion of females on HAART was twofold than that of males in Ilorin, Nigeria [27].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The value of co-trimoxazole in reducing the morbidity and mortality associated with HIV infection has been well established through clinical trials conducted in industrialized 5,6 and developing countries. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] CTXp is associated with a 25-46% reduction in mortality among individuals infected with HIV in sub-Saharan Africa, even in areas with high bacterial resistance to the antibiotic. These improvements in survival have been accompanied by substantial reductions in severe disease events and in the number of hospital admissions linked to invasive bacterial disease, pneumonia, malaria and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%